Frailty Scores and Ethical Decision‐Making in Critical Care: Lessons From the COVID ‐19 Pandemic - Chukwuka Elendu; Chidera A. Okezie‐Okoye; Ahmed I. Ali; Emeka H. Okolo; Mirabel A. Bell‐Gam; Kiranraj Ravikumar; Favour K. Mbakwe (Clinical Case Reports, 2026)
ABSTRACT Frailty scores should support, not replace, individualized critical care decisions, as the COVID‐19 pandemic exposed the ethical limitations of rigid frailty‐based triage, particularly among older adults and individuals with chronic disability. Meaningful recovery may occur despite severe illness, reinforcing the importance of patient autonomy, multidisciplinary assessment, and holistic clinical judgment.